2011
DOI: 10.1002/bit.23040
|View full text |Cite
|
Sign up to set email alerts
|

Possible Effect From Shear Stress on Maturation of Somatic Embryos of Norway Spruce (Picea abies)

Abstract: Somatic embryogenesis is the only method with the potential for industrial scale clonal propagation of conifers. Implementation of the method has so far been hampered by the extensive manual labor required for development of the somatic embryos into plants. The utilization of bioreactors is limited since the somatic embryos will not mature and germinate under liquid culture conditions. The negative effect on mature embryo yields from liquid culture conditions has been previously described. We have described th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…To further elucidate the potential negative effects of liquid culture conditions on somatic embryo development, the effects of fluid shear stress on development of PEMs have been studied in a flow cell system. It was demonstrated that maintaining PEMs under shear stress from fluid flow conditions prevents directional growth of the PEMs (Sun et al 2010 ) and furthermore, that PEMs under such conditions are less likely to mature (Sun et al 2011 ). Temporary immersion bioreactor systems offer an ideal liquid-based system, providing benefits from liquid culture medium with respect to accessibility to culture components.…”
Section: Discussionmentioning
confidence: 99%
“…To further elucidate the potential negative effects of liquid culture conditions on somatic embryo development, the effects of fluid shear stress on development of PEMs have been studied in a flow cell system. It was demonstrated that maintaining PEMs under shear stress from fluid flow conditions prevents directional growth of the PEMs (Sun et al 2010 ) and furthermore, that PEMs under such conditions are less likely to mature (Sun et al 2011 ). Temporary immersion bioreactor systems offer an ideal liquid-based system, providing benefits from liquid culture medium with respect to accessibility to culture components.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly for scale up processes in bioreactors, conifers appear to prefer a solid substrate to support directional growth of the most developmentally advanced PEMs (Sun et al, 2010). A polarized early stage PEM structure which represents the more developed early stages of somatic embryos is most likely to respond to the maturation treatment (Sun et al, 2011). Therefore, temporary immersion bioreactors providing solid support for culture growth by the mesh constituting the bottom of the bioreactor insert promotes directional growth of PEMs and formation of polarized early stage embryos and can thus have advantages over other types of bioreactors based on complete immersion and agitation of the culture.…”
Section: Automation Of Different Steps Of the Se Processmentioning
confidence: 99%
“…Between the mid-1980s and the early 1990s, the successful application of the somatic embryogenesis method for the micropropagation of both spruce species was achieved (Hakman et al 1985;Chalupa 1985;Budimir and Vujičić 1992). Thereafter, P. abies became the model species for the study of various aspects of conifer somatic embryogenesis Lipavská et al 2000;Malá et al 2009;Sun et al 2011;Bříza et al 2013;Hazubska-Przybył et al 2013). Few studies have investigated the somatic embryogenesis of P. omorika (Tramisak-Milaković et al 1999;Leljak-Levanić et al 2009;Hazubska-Przybył et al 2010), a more unique spruce species because of its endemic and relict character (Vujičić and Budimir 1995;Ballian et al 2006).…”
Section: Introductionmentioning
confidence: 99%